PERTUKARAN INFORMASI TERHADAP PENANGANAN STUNTING DI INDONESIA DAN KOREA SELATAN - Sari, Ninuk Permata; Nurrachmi, Intan; Jamilah, Lina; Nurliawati, Nita; Zaeni, Mutiara Refanisa; Nasawi, Avicenna Mujtahid (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
In Indonesia and South Korea, stunting is still a serious nutritional problem. However, there is a significant difference in the prevalence of stunting where the incidence of stunting in Indonesia is still quite high even though there has been a decline, namely from 24.4% in 2021 to 21.6% in 2022. Meanwhile, the stunting rate in South Korea is very low, even the lowest in East Asia with only 2.5% of children under 5 years of age experiencing stunting. The purpose of this community service is to exchange information about the policies of the two countries in dealing with stunting and to study the good practices of the application of Indonesian government policies carried out by the PKK mothers of Taman Sari Village by creating the Cikalat (Love for Toddlers) innovation program. The community service method is carried out through lectures, panel discussions and questionnaire. Community service activities were carried out in Taman Sari Village, Bandung City on May 14, 2025. The target of the service was PKK mothers and the community of Taman Sari Village, Bandung City. The conclusion of this activity is that information related to policies between countries is conveyed well and ends with the signing of the Implementation Agreement from the three universities involved.ABSTRAKDi negara Indonesia dan Korea Selatan, stunting masih menjadi masalah gizi yang cukup serius. Meski demikian, terdapat perbedaan prevalensi stunting yang cukup signifikan dimana kejadian stunting di Indonesia masih cukup tinggi walaupun sudah terjadi penurunan yaitu dari 24,4% di tahun 2021 menjadi 21,6% di 2022. Sementara itu, angka stunting di Korea Selatan sangat rendah, bahkan terendah di Asia Timur dengan hanya 2,5% anak di bawah usia 5 tahun yang mengalami stunting. Tujuan pengabdian kepada masyarakat ini adalah untuk pertukaran informasi tentang kebijakan kedua negara dalam menangani stunting serta mempelajari praktik baik aplikasi kebijakan pemerintah Indonesia yang dilakukan oleh ibu-ibu PKK Kelurahan Taman Sari dengan menciptakan program inovasi Cikalat (Cinta ka Balita). Metode pengabdian kepada masyarakat dilakukan dengan ceramah, diskusi panel dan kuesioner. Kegiatan pengabdian masyarakat dilaksanakan di kelurahan Taman Sari kota Bandung pada tanggal 14 Mei 2025. Sasaran pengabdian adalah ibu-ibu PKK serta masyarakat kelurahan Taman Sari kota Bandung. Kesimpulan dari kegiatan ini adalah informasi terkait kebijakan antar negara tersampaikan dengan baik serta diakhiri dengan penandatangan Implementation Agreement dari tiga Universitas yang terlibat.